2014
DOI: 10.3390/ijms150915456
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Forces Induce Changes in VEGF and VEGFR-1/sFlt-1 Expression in Human Chondrocytes

Abstract: Expression of the pro-angiogenic vascular endothelial growth factor (VEGF) stimulates angiogenesis and correlates with the progression of osteoarthritis. Mechanical joint loading seems to contribute to this cartilage pathology. Cyclic equibiaxial strains of 1% to 16% for 12 h, respectively, induced expression of VEGF in human chondrocytes dose- and frequency-dependently. Stretch-mediated VEGF induction was more prominent in the human chondrocyte cell line C-28/I2 than in primary articular chondrocytes. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…On other hand Herzog et al [29] stated that increased blood vessel formation was observed in TD in which the low level of Flk-1 was described as one of the rate-limiting factors of blood-vessel formation that resulted in the unvascularized growth plate. An in vitro model of human chondrocyte culture also showed an increase in the expression level of VEGF [30,31]. Thiram appeared to be effective in up-regulating VEGF expression, suggesting that thiram has proangiogenic activity [21].…”
Section: Discussionmentioning
confidence: 89%
“…On other hand Herzog et al [29] stated that increased blood vessel formation was observed in TD in which the low level of Flk-1 was described as one of the rate-limiting factors of blood-vessel formation that resulted in the unvascularized growth plate. An in vitro model of human chondrocyte culture also showed an increase in the expression level of VEGF [30,31]. Thiram appeared to be effective in up-regulating VEGF expression, suggesting that thiram has proangiogenic activity [21].…”
Section: Discussionmentioning
confidence: 89%
“… b ; Beckmann et al . ). TGF‐β isoforms and their receptors have broad biological functions and are involved in different processes in tendon tissue, including development, growth, healing, adaptation and tissue homeostasis (Fenwick et al .…”
Section: Discussionmentioning
confidence: 97%
“…Thiram is lipophilic in nature and combined with the cell membrane to cause cytotoxicity, bone formation disorder, cartilage cell damage and immune depressions. It can also cause membrane damage, bone morphogenic inactivation and inhibit angiogenesis [12,13]. In TD, a large number of the cartilage cell damage is due to the apoptosis process and abnormal protein secretion in the cartilage cells, causing a decrease in the cartilage extracellular matrix degradation rate, which limits the space for bone deposition [14,15].…”
Section: Discussionmentioning
confidence: 99%